On the design of hybrid and polymorphic routing protocols for mobile ad hoc networks - Chen, Lei (2009)
With the rapid growth of the development of wireless communication technology, we witness the increase in the popularity in the research of wireless Mobile Ad hoc Networks (MANETs). Since MANETs are networks with no fixed infrastructure, nodes within a MANET communicate with each other through a multi-hop route. Thus, effective routing protocols for MANETs are in urgent need to realize MANETs. This thesis introduces new concepts and designs for routing protocols in MANETs. We first design routing protocols for MANETs using the hybrid approach. We propose two hybrid routing protocols, namely, ZODMRP and ZMAODV. The hybrid approach attempts to combine the benefits of proactive and reactive routing protocols into a single routing protocol. This combination allows a node implementing a particular hybrid routing protocol to operate in two different routing behaviors at the same time.